EFFLUENTS FROM INDUSTRIAL PROCESSING OF THE FOOD OF ANIMAL ORIGIN AS MEDIA FOR BIOCONTROL AGENTS PRODUCTION - Pajčin, Ivana S.; Vlajkov, Vanja; Dujković, Tatjana; Grahovac, Jovana (Journal on Processing and Energy in Agriculture, 2023)
ABSTRACT Intensive food production to feed the growing human population requires significant material and energy resources, simultaneously generating large amounts of waste, whose treatment adds an additional cost to the overall production process. Wastewaters arising from meat and dairy processing industries contain large amounts of organic and inorganic nutrients, which present a heavy environmental burden, but, on the other hand, could serve as nutrient sources for microbial growth. The aim of this study was to investigate suitability of meat processing wastewater and whey from dairy industry as media for growth of biocontrol strain Bacillus velezensis IP22. The both waste-based media have contributed to antibacterial and antifungal activity to a similar degree, with highly comparable inhibition zone diameters against Xanthomonas campestris, Xanthomonas euvesicatoria and Aspergillus flavus. Furthermore, biocontrol activity of the cultivation broths obtained using the waste-based media was slightly lower compared to the nutrient broth medium, suggesting the possibility to replace the expensive chemically defined medium with a complex medium alternative. This approach based on circular economy principles promotes responsible resource utilization through reuse of food industry effluents for production of value added products, opening a chapter of possibilities to establish industrial symbiosis network between companies in different industry branches.